2016
DOI: 10.5935/1518-0557.20160042
|View full text |Cite
|
Sign up to set email alerts
|

The effects of storing and transporting cryopreserved semen samples on dry ice

Abstract: ObjectiveThis study aimed to test the effects on sperm viability of transporting cryopreserved semen samples on dry ice.MethodsTwenty normozoospermic semen samples were cryopreserved and divided into five groups. The samples in Group 1 were immersed in liquid nitrogen throughout the experiment in cryogenic storage tanks; the cryopreserved straws in Group 2 were placed in a Styrofoam box containing dry ice and kept under these conditions for 48 hours; the samples in Group 3 were kept for 48 hours on dry ice und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…In this study, maintenance of motility at a range of 38% to 100% and vitality at 65% to 97% after cryopreservation, among donor samples, indicated that each individual may have a different response to cryopreservation. Similar results were reported by Til et al . (2016) , who observed reduction rates of 19% to 94% in motility and from 27% to 80% in vitality.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, maintenance of motility at a range of 38% to 100% and vitality at 65% to 97% after cryopreservation, among donor samples, indicated that each individual may have a different response to cryopreservation. Similar results were reported by Til et al . (2016) , who observed reduction rates of 19% to 94% in motility and from 27% to 80% in vitality.…”
Section: Discussionsupporting
confidence: 93%
“…The same was found in the present study, suggesting that -80°C is not able to keep sperm cells in the latency state obtained by the cryopreservation process, since the continuous drop in motility and vitality values resembles those observed by Paiva (2010) , when evaluating sperm survival time. Til et al (2016) found similar results when evaluating the dry ice (-79°C) transport of cryopreserved samples, proving the ineffectiveness of this temperature in maintaining semen viability.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…More recent papers showed that bovine semen could be maintained for short time on dry ice [34] or at −80°C [35] but not at −30°C, without losing its ability to fertilise eggs. In contrast, human spermatozoa stored and transported in dry ice quickly loose their motility and vitality [36]. Short term exposure (more than 24 h) to dry ice compromised spermatozoa motility regardless of type of cryoprotectant used [37].…”
Section: Discussionmentioning
confidence: 99%